Impact of pH and butyric acid on butanol production during batch fermentation using a new local isolate of Clostridium acetobutylicum YM1 - Najeeb Kaid Nasser Al-Shorgani (Saudi Journal of Biological Sciences, 2018)
The effect of pH and butyric acid supplementation on the production of butanol by a new local isolate of Clostridium acetobutylicum YM1 during batch culture fermentation was investigated. The results showed that pH had a significant effect on bacterial growth and butanol yield and productivity. The optimal initial pH that maximized butanol production was pH 6.0 ± 0.2. Controlled pH was found to be unsuitable for butanol production in strain YM1, while the uncontrolled pH condition with an initial pH of 6.0 ± 0.2 was suitable for bacterial growth, butanol yield and productivity. The maximum butanol concentration of 13.5 ± 1.42 g/L was obtained from cultures grown under the uncontrolled pH condition, resulting in a butanol yield (YP/S) and productivity of 0.27 g/g and 0.188 g/L h, respectively. Supplementation of the pH-controlled cultures with 4.0 g/L butyric acid did not improve butanol production; however, supplementation of the uncontrolled pH cultures resulted in high butanol concentrations, yield and productivity (16.50 ± 0.8 g/L, 0.345 g/g and 0.163 g/L h, respectively). pH influenced the activity of NADH-dependent butanol dehydrogenase, with the highest activity obtained under the uncontrolled pH condition. This study revealed that pH is a very important factor in butanol fermentation by C. acetobutylicum YM1.